An underground air-route temperature prediction model for ultra-deep coal mines - Zhu, S.; Wu, S.; Cheng, Jianwei; Li, S.; Li, M. (2015)
Due to modern mining methods deployed in recent years, production of coal mines has been expanded significantly compared to thirty years ago. As a consequence, the mining depth of coal mines is becoming ever deeper. A common world-wide problem that underground coal mines are currently experiencing is the hazard caused by the underground hot environment, which also promotes a great need of reliable mitigation measures to assist mine operators controlling the heat stress for miners as well as maintaining the normal operation of the mine. In this paper, a model for underground air-route temperature prediction in ultra-deep mines based on previous findings was developed. In developing this model, the idea of heat balance was used to establish the temperature calculation equation. Various underground heat sources (air compress, wall oxidation, underground heat, machinery, etc.) are covered in the model to improve the prediction accuracy. In addition, a PC-based numerical tool was also developed to aid users using such a mathematical model. Finally, a few temperature measurements for an ultra-deep underground coal mine were performed to demonstrate the applicability of the proposed mathematical prediction model.